Post-COVID-19 febrile infection-related epilepsy syndrome in a child successfully treated with a multimodal approach - Anuar, Muhamad Azamin; Musa, Husna; Murugesu, Sumitha; Mohamed, Ahmad Rithauddin; Khoo, Teik Beng (Malaysian Medical Association, 2023)
Post-infectious inflammatory syndrome following COVID-19 infection has been increasingly reported affecting multiple organs. Neurological presentations such as encephalopathy and seizures are common. Recently, during the surge of Omicron variant cases, we recorded a high prevalence of febrile seizure cases all over the country. Most febrile seizures are benign; however, a small proportion that progress into refractory epilepsy syndrome and require intensive care management. We report a 2-year-old child with refractory status epilepticus following COVID-19 infection, who was diagnosed and treated as febrile infection-related epilepsy syndrome (FIRES). A multimodal approach was adopted, using immunotherapy tocilizumab and ketogenic diet. The child currently has good seizure control but requires neurorehabilitation to improve ambulation, behaviour and cognition. This case highlights the importance of quick recognition of FIRES and its successful multimodal management that included tocilizumab.